KEDUDUKAN KOMPILASI HUKUM ISLAM DALAM POLITIK HUKUM KELUARGA DI INDONESIA - melinda, lindamelinda; Nurrohman, Nurrohman (El-Ahli : Jurnal Hukum Keluarga Islam, 2024)
The Compilation of Islamic Law is the first codification of Islamic law in Indonesia which is used as a legal guide for Religious Court Judges to decide cases related to marriage, endowments and inheritance. However, is this compilation of Islamic law considered binding law or is it just a guide for judges? Therefore, the author intends to research the position of the Compilation of Islamic Law in family law politics in Indonesia using qualitative research methods in the form of literature studies sourced from books, laws, journal articles and other sources that are appropriate to the material studied. And the research results show that the position of this Compilation of Islamic Law in the Hierarchy of National Legislation until now is still in the form of Presidential Instruction Number 1 of 1991. Meanwhile, the Presidential Instruction is only limited to providing direction, guiding, mentoring, in terms of carrying out tasks and work. So if you look at article 7 of Law Number 12 of 2011, this Presidential Instruction does not include the Type, Hierarchy and Content of statutory regulations. Therefore, the position of the Compilation of Islamic Law in family law politics in Indonesia is still weak. However, what is meant by weak here is not weak in terms of the content of the Compilation of Islamic Law but only its position. However, this Compilation of Islamic Law is really needed and very important for the Muslim community, therefore the author hopes that its position can be improved so that it becomes a law that is not just a guideline for judges, but a law that Muslims can follow. in Indonesia.